EVALUASI JALUR PEDESTRIANIAN SEBAGAI PENUNJANG URBAN TOURISM (Studi Kasus : Jalur Pedestrian JL.Jendral Sudirman Yogyakarta) - Rekta Deskarina (Bajang Institute, 2025)
Demand of physical infrastructure is very important to support easy accessibility and the development of activities in urban areas which definitely can improve attractiveness of urban areas. Jenderal Sudirman Street Yogyakarta, which has various functions for activities in the road space such as office, business, and tourism activities, demands the arrangement of pedestrian paths as a complement to a city as well as supporting urban tourism activities that are able to provide comfort for pedestrians. The purpose of this research is to obtain a comprehensive overview of the condition of the Jenderal Sudirman Street pedestrian path and its supporting facilities. The data analysis method that being used is to analyze the comparison of existing conditions with standard criteria referring to Minister of Public Works Regulation No. 03 of 2014 concerning Guidelines for Planning, Providing and Utilizing Pedestrian Network Infrastructure and Facilities in Urban Areas. The results of this research indicate that the condition of the existing pedestrian path on Jenderal Sudirman Street generally meets the standard criteria in terms of availability of facilities and quality. However, accessibility for disabled people is not suitable for pedestrians with disabilities. At several points there are damaged/broken guiding block tiles, disconnected guiding block paths, and there are still motorbikes parked on the guiding block paths. Attention is needed to the arrangement of guiding blocks to provide comfort and aesthetics in urban spaces for all pedestrians, including people with disabilities, thereby supporting urban tourism activities